SOCIAL MOVEMENT IN FARMERS’ RESISTANCE (A CASE STUDY OF THE UNITED SIMALINGKAR FARMERS UNION (SPSB)IN SIMALINGKAR A, DELISERDANG) - Sry Lestari Samosir; Badaruddin Badaruddin; Henri Sitorus; Muba Manihuruk; Faisal Andri Mahrawa (Lafadz Jaya Publisher, 2023)
In 2017, farmers in Simalingkar A Village, Deliserdang, and security forces were involved in clashes. Many farmers were injured, and some were detained at the local police station. Until now, there has been no resolution of the conflict to lead to peace. The farmer conflict in Simalingkar A Village illustrates how complicated the agrarian conflict is in Indonesia, especially in North Sumatra. This research is a case study that provides an in-depth investigation into a single case or a small number of cases to better understand the conflict between farmers and PTPN II. With the existing limitations, farmers in Simalingkar who are members of the Simalingkar United Farmers Union (SPSB) made efforts to accommodate the hopes and demands of farmers to create a solution that benefits both parties. Based on the analysis using this theory, it can be concluded that the SPSB played a role in resolving the conflicts. They made efforts using several channels of interest articulation, including rallies, demonstrations, lobbying, and walking from Medan to Jakarta.